2018
DOI: 10.1038/s41467-018-04220-w
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule fate of HIV-1 envelope reveals late-stage viral lattice incorporation

Abstract: Human immunodeficiency virus type 1 (HIV-1) assembly occurs on the inner leaflet of the host cell plasma membrane, incorporating the essential viral envelope glycoprotein (Env) within a budding lattice of HIV-1 Gag structural proteins. The mechanism by which Env incorporates into viral particles remains poorly understood. To determine the mechanism of recruitment of Env to assembly sites, we interrogate the subviral angular distribution of Env on cell-associated virus using multicolor, three-dimensional (3D) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 42 publications
9
50
1
Order By: Relevance
“…We could also measure that the Gag-Gag interaction mediated by CA-CA dimerization was representing only a third of the Gag attractive energy while the NC-RNA platform represents two third of it [45]. Furthermore, coarse grain modeling predicted recently that the presence of the vRNA lowered the necessary SP1-CA hexameric interaction energy down to 3 kT to achieve correct HIV-1 assembly [61], thus in perfect agreement with our findings in The spatiotemporal aspects of Env incorporation into HIV-1 virions during particle assembly was also studied recently by Buttler et al, [62] using interferometric PALM (iPALM, [63]). They reported that Env was incorporated in preformed Gag lattices to the neck of the assembling virion, as determined by the Env angular distribution on the surface of cell-associated virus.…”
Section: Towards a Real Time Molecular Description Of Hiv Assembly Insupporting
confidence: 91%
“…We could also measure that the Gag-Gag interaction mediated by CA-CA dimerization was representing only a third of the Gag attractive energy while the NC-RNA platform represents two third of it [45]. Furthermore, coarse grain modeling predicted recently that the presence of the vRNA lowered the necessary SP1-CA hexameric interaction energy down to 3 kT to achieve correct HIV-1 assembly [61], thus in perfect agreement with our findings in The spatiotemporal aspects of Env incorporation into HIV-1 virions during particle assembly was also studied recently by Buttler et al, [62] using interferometric PALM (iPALM, [63]). They reported that Env was incorporated in preformed Gag lattices to the neck of the assembling virion, as determined by the Env angular distribution on the surface of cell-associated virus.…”
Section: Towards a Real Time Molecular Description Of Hiv Assembly Insupporting
confidence: 91%
“…Recent evidence suggests a role for recycling in Env incorporation (15)(16)(17) and many studies have explored the role of trafficking motifs in the gp41 CT in promoting the proper spatio-temporal localization of Env during assembly (1,2,18,19), but the role of Env recycling in Env incorporation is not well-defined. Wild-type (WT) HIV-1 has an average of ~10 Env trimers per virion (20) and truncation of the gp41 CT generally results in a 10-fold decrease in Env incorporation in physiologically relevant cell types (which we refer to as being non-permissive to gp41 CT truncation) (21).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of regulation seems to be cell-type and CT dependent. For example, in the non-permissive T-cell line CEM-A, WT Env is localized at the neck of the budding particle while truncation of the gp41 CT results in a more uniform Env distribution around the virus particle (19). In the permissive COS7 fibroblast-like cell line, both WT and CT-truncated Env are evenly distributed around the virus particle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those hexameric structures also have implications for Env incorporation in immature HIV-1 virions [54,55,[57][58][59]. HIV-1 Env incorporation into immature virions is believed to be directed by the long cytoplasmic tail (CT) of gp41 and steric trapping within these MA hexamers of trimers [13,[60][61][62][63][64][65]. This process is highly regulated, considering the low number of Env incorporated into released particles (7-14 trimers) [66].…”
Section: Matrix (Ma P17)mentioning
confidence: 99%